1994
DOI: 10.1016/0735-1097(94)90374-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transatrial mitral commissurotomy: Immediate and intermediate results

Abstract: Percutaneous transatrial mitral commissurotomy is an effective, safe procedure with gratifying intermediate results. It should be considered the treatment of choice for rheumatic mitral stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
1
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 37 publications
8
43
1
5
Order By: Relevance
“…Previous studies have confirmed that this procedure is highly successful with a low complication rate and significant short-and long-term improvement in both hemodynamics and patient symptoms. [14][15][16] The present study demonstrates that PTMC produces significant morphologic and hemodynamic changes in the mitral valve. We found that PTMC produced a significant increase in MVA and a significant splitting of both mitral commissures.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have confirmed that this procedure is highly successful with a low complication rate and significant short-and long-term improvement in both hemodynamics and patient symptoms. [14][15][16] The present study demonstrates that PTMC produces significant morphologic and hemodynamic changes in the mitral valve. We found that PTMC produced a significant increase in MVA and a significant splitting of both mitral commissures.…”
Section: Discussionmentioning
confidence: 81%
“…A recent report reviewing transatrial mitral commissurotomy in 600 patients with rheumatic mitral stenosis cited a very low left atrial perforation rate of I %. 15 Left atrial enlargement has been felt to attenuate the risk of atrial perforatione6 However, distorted septal anatomy may also increase the inadvertent perforation rate, for example, when certain valvular diseases displace the fossa ovalis from its normal position ( e g , in mitral stenosis, the fossa is usually displaced inferiorly).1s Multivariate analysis is required to verify whether the risk of atrial perforation during transseptal catheterization increases or decreases depending upon whether there is atrial dilatation and associated septal anatomy distortion or whether atria are normal.…”
Section: Discussionmentioning
confidence: 99%
“…• Sucesso: aumento da área valvar ≥ 25% da área inicial e área valvar mitral final ≥ 1,5 cm², na ausência de insuficiência mitral grave [6][7][8][9][10][11] .…”
Section: Definiçõesunclassified
“…• Reestenose ecocardiográfica: área valvar mitral no seguimento tardio, avaliada pela planimetria e/ou pelo tempo de meia pressão (PHT), < 1,5 cm², com perda ≥ 50% do ganho inicial [7][8][9] .…”
Section: Definiçõesunclassified